The birth of radio broadcasting: The matrix of science, technology and communication in the western world. (1st October 2013) - Barboutis, Christos
Between the end of the nineteenth century and the beginning of the twentieth, the possibilities of three different types of wireless communication technology were made evident to the western world. Instead of uncritically presenting US-based accounts, this article delineates the relationship between radio technology and communication, moulded by the notion of modern science, which bears as a consequence the establishment of broadcasting as a mass phenomenon in western societies. The above-mentioned relationship is explained without downplaying at the same time the existence of relativism in particular social settings. Thus, the article is underpinned by the interplay among the cultural, economic and political factors that finally led to the development of radio broadcasting during the 'Roaring Twenties'.